1998
DOI: 10.1023/a:1021456731470
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The finding that stress-induced locomotor activity exhibited a significant strain x time interaction in the LS x SS RI strains prompted examination of QTL influencing this behavior as a function of time. The degree of genetic determination for locomotor activity was 0.26 for the first 5 min and decreased to 0.16 for the last 5 min of a 30-min test but the number of genetic factors stayed relatively constant (three or four) across time. A QTL point analysis revealed a total of 15 QTL, 5-8 per 5-min time block. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Like anxiety-related behavior, locomotor activity in mice has been found to be polygenic, with the majority of mouse chromosomes being identified to carry QTLs affecting locomotor activity (Radcliffe et al, 1998). This polygenic nature was also found for the temporal aspect of locomotion as significant/ suggestive evidence was found in 11 of the 20 tested consomic lines when analyzing the AUC combined with latencies (Fig.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Like anxiety-related behavior, locomotor activity in mice has been found to be polygenic, with the majority of mouse chromosomes being identified to carry QTLs affecting locomotor activity (Radcliffe et al, 1998). This polygenic nature was also found for the temporal aspect of locomotion as significant/ suggestive evidence was found in 11 of the 20 tested consomic lines when analyzing the AUC combined with latencies (Fig.…”
mentioning
confidence: 78%
“…Linkage studies aimed at the identification of chromosomal regions that modulate the change of behavior across time however suggest that the initial behavioral response is most closely linked to genotype. Radcliffe et al, (1998) for example identified different chromosomes on different time points when assessing locomotor activity in five-minute epochs of a 30-minute OF-trial, in a panel of long-sleep and short-sleep recombinant inbred strains of mice. They found that the coefficient of genetic determination decreased over the course of thirty minutes, leading them to suggest that an initial response to a novel environment is more dependent on genotype, whereas environmental influences become increasingly influential to behavioral output (Radcliffe 5 et al, 1998).…”
mentioning
confidence: 99%